Common hematological and biochemical parameters for predicting urinary tract infections in geriatric patients with hip fractures - Tang, Wanyun; Yao, Wei; Wang, Wei; Lv, Qiaomei; Ding, Wenbo; He, RenJian (Frontiers in Medicine, 2024)
Background This study aims to discern the significance of common hematological and biochemical parameters for predicting urinary tract infections in geriatric patients with hip fractures. Methods Multivariable logistic regression and propensity score-matched analyses were conducted to calculate adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for UTIs. The abilities of these parameters to predict UTIs were evaluated by receiver operating characteristic (ROC) curves. Dose–response relationships were assessed by categorizing hematological and biochemical parameters into quartiles. Subgroup analyses were further explored to investigate the relationship between these parameters and urinary tract infections. Results Out of the 1,231 participants, 23.2% were diagnosed with UTIs. Hyperglycemia, hypoproteinemia and hyperglobulinemia were risk factors for UTIs in multivariate analysis. After propensity score matching, hyperglycemia (OR 2.14, 95% CI 1.50–3.05, p < 0.001), hypoproteinemia (OR 1.75, 95% CI 1.18–2.63, p = 0.006), and hyperglobulinemia (OR 1.38, 95% CI 0.97–1.97, p = 0.074) remained significantly associated with increased odds of urinary tract infections. ROC curve analyses showed moderate predictive accuracy of blood glucose, albumin and globulin for UTIs, with areas under the curves of 0.714, 0.633, and 0.596, respectively. Significant dose–response relationships were observed between these parameters and UTIs. The associations were consistent in subgroup analyses. Conclusion Blood glucose, albumin and globulin levels can facilitate early identification of geriatric hip fracture patients at high risk of UTIs. These easily obtainable hematological and biochemical parameters provide a practical clinical prediction tool for individualized UTI prevention in this population.